Relationship between selected intellective and non-intellective factors and achievement scores in high school physics test - Cruz, Milagros A. 1945- ([s.n.], 1971)
This paper presented a look into the Physics achievement of senior students enrolled during the academic year 1969-1970 in Ramon Magsaysay (Cubao) High School. The sample consisted of 200 seniors belonging to the even sections. The basic sources of data are the school records, personal data questionnaire, scores in the Bureau of Public School Mathematics and English Test, scores in the UP Physics test, and scores in the Otis Mental Ability Test.